2020
DOI: 10.1037/pspa0000195
|View full text |Cite
|
Sign up to set email alerts
|

Moral cleansing as hypocrisy: When private acts of charity make you feel better than you deserve.

Abstract: Moral cleansing as hypocrisy: When private acts of charity make you feel better than you deserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 118 publications
2
19
0
Order By: Relevance
“…Furthermore, privately engaging in good deeds can make you appear hypocritical, if your good deeds are inconsistent with your public transgressions. In a recent series of studies (O'Connor et al, 2020), subjects judged the founder of a pro-infidelity website to be hypocritical for privately remaining faithful to his wife. Or, in another scenario, subjects deemed a tobacco company executive hypocritical for secretly donating to anti-smoking causes.…”
Section: Does Moral Engagement Inevitably Create a Hypocrisy Liability?mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, privately engaging in good deeds can make you appear hypocritical, if your good deeds are inconsistent with your public transgressions. In a recent series of studies (O'Connor et al, 2020), subjects judged the founder of a pro-infidelity website to be hypocritical for privately remaining faithful to his wife. Or, in another scenario, subjects deemed a tobacco company executive hypocritical for secretly donating to anti-smoking causes.…”
Section: Does Moral Engagement Inevitably Create a Hypocrisy Liability?mentioning
confidence: 99%
“…Recent evidence that people see hypocrisy in the absence of false signaling would seem to pose a challenge to this false signaling theory. For example, recall that sin-industry promoters whose private behavior is virtuous-such as the founder of a pro-infidelity website who privately stays faithful to his wife or a tobacco company executive who privately donates to anti-smoking causes-are judged as hypocritical (O'Connor et al, 2020), even though their moral acts are not public and are thus unlikely to earn them undeserved reputational benefits. However, if one draws a distinction between hypocrisy and negative moral evaluation, it becomes clear that such examples do not necessarily negate the proposal that false signaling is the key to why people dislike hypocrites.…”
Section: The Role Of False Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, people's behavior often exhibits a positive effect on others. Furthermore, studies have reported that people's moral identity is threatened when moral standards conflict with self-interest (Valdesolo and Desteno, 2007;Monin et al, 2009;O'Connor et al, 2020). To reduce cognitive conflict, people often adopt different approaches: when encountering moral standards, people usually avoid MH behaviors; when these behaviors are not avoided, they lower their moral standards to rationalize their hypocritical behavior (López-Pérez and Spiegelman, 2013;Kish-Gephart et al, 2014;Abdai and Miklósi, 2016).…”
Section: Effects Of the Behavior Of In-group Or Out-group Strangers Omentioning
confidence: 99%
“…First, people adopt harsher and stricter standards of moral judgment for others than those they adopt for themselves (Valdesolo and DeSteno, 2008;Lammers et al, 2010), and this type of hypocrisy occurs at the intrapersonal level. Second, at the interpersonal level, hypocrisy is manifested in people's morality standards, which are inconsistent with their actual behavior; that is, their actual behavior fails to meet their claimed moral requirements of behavior (Watson and Sheikh, 2008;O'Connor et al, 2020). Batson et al (1997) investigated hypocrisy and explained the cause for moral people apparently behaving immorally.…”
Section: Introductionmentioning
confidence: 99%